Decision-making executive function profile and performance in older adults with major depression: a case-control study. (14th July 2022) - Siqueira, Alaise Silva Santos; Biella, Marina Maria; Borges, Marcus Kiiti; Mauer, Sivan; Apolinario, Daniel; Alves, Tânia Côrrea de Toledo Ferraz; Jacob-Filho, Wilson; Oude Voshaar, Richard C.; Aprahamian, Ivan
Abstract: Objectives: Decision making (DM) is a component of executive functioning, essential for choosing appropriate decisions. Executive dysfunctioning is particularly common in late-life depression, however the literature is scarce on DM. This case-control study aimed to evaluate the DM profile and performance in participants with and without unipolar major depression. Method: The DM profile and performance were assessed by the Melbourne Decision Making Questionnaire and the Iowa Gambling Task (IGT), respectively, in three groups of older adults from a university-based geriatric psychiatry clinic, i.e. current depression ( n  = 30), remitted depression ( n  = 43) and healthy controls ( n  = 59). The Hamilton Depression scale (HAM-D) 21 items, the Hamilton Anxiety scale, and the Mini-Mental State Examination were used to access depressive symptoms, anxiety symptoms, and cognitive impairment, respectively. Multinomial, nominal and binary logistic regression was used to evaluate the associations between depression, depressive symptomatology and DM. Results: In comparison to the control group, patients with current depression presented higher scores in buck-passing and proscratination DM profiles. In the hypervigilance profile, there was a significant difference between current and remitted depression groups. A higher value ​in the HAM-D scale increased the probability of disadvantageous DM profiles. Depressive patients showed a tendency of a higher mean score in both disadvantageous decks (A and B) of IGT. Patients with current depression showed a worse performance compared to the remitted depression group in the IGT netscore. Conclusion: Older adults with current depression showed DM profiles considered maladaptive or disadvantageous compared to both remitted depression and healthy controls groups.